PENINGKATAN KEMAMPUAN SOSIAL MELALUI MEDIA DRUM BAND DENGAN TEKNIK GERAK DAN LAGU PADA ANAK KELOMPOK B TK AL-KAHFI KECAMATAN RANCASARI KOTA BANDUNG TAHUN AJARAN 2017-2018 - Zulfi Nursaadah; Ari Abdul Kohar Rahmatullah (EduChild: Majalah Ilmiah Pendidikan, 2021)
PENINGKATAN KEMAMPUAN SOSIAL MELALUI MEDIA DRUM BAND DENGAN TEKNIK GERAK DAN LAGU PADA ANAK KELOMPOK B TK AL-KAHFI KECAMATAN RANCASARI KOTA BANDUNG TAHUN AJARAN 2017-2018OlehZulfi Nur Sa’adah1Ari Abdul Kohar Rahmatullah2Program Studi PG-PAUD Universitas Islam NusantaraABSTRACTThis research is motivated by the low level of self-conscious children, children who have not been able to obey the rules and lack of responsibility for their work and children who do not have prosocial behavior. This study aims to obtain an overview of the improvement of the social abilities of eraly childhood through drum band media with snarling and song techniques in children in group B in Al-Kahfi Kindergarten, Rancasari Sub-District, Bandung City. The method used in the research carried out in two cycles in an effort to improve the process of management which is its responsibility. The research design used is the model prposed by Kemmis an Mc Teggart, in this model each cycles consists of several steps, namely planning, implementation, observation, and reflection. The subject of this study were all students in group B of the Al-Kahfi Kindergarten in Rancasari Sub-District, Bandung City, amounting to 16 children. Data collection techniques in this study used interview, observation, documentation, and assessment instruments. The results observation were analyzed by qualitative qualification techniques, which consisted of four components, namely collecting data, and conclusions. The results of data analysis showed that there was a significant increase in group B sosial abilities through the application of drum band media with motion and song techniques, in the criteria for children not yet developed, 56,25% in the criteria of children began to grow, by 0% in the criteria for developing children are very good, and have increased, the social ability of children after being given action in  cycle I in criteria yet. Growing down to 6,25% in criteria starting to develop in the first cycle increased to 68,75% in criteria developed according to expectations in cycles I is still fixed at 0%, while in cycle II  has reached a corresponding increase which is expected to be seen in criteria no developed in cycle II decreased to 0%, in muly criteria developed in cycles II decreased to 0%, deep criteria develop according to expectations in the second cycle to achieve 25%, and within. The criteria for excellent pepper development cycles II greatly increased to 75%. So applying drum band media with motion and song techniques can improve children’s social skills in self-awareness behavior, have a sense of responsibility for themselves and others and can have prosocial behavior. So that it can be concluded that there was an increase in children’s social skills after using drum band media with motion and song techniques.